Child marriage and health disparities in adulthood: the differential risk of untreated hypertension among young adult women in India - Biplab Kumar Datta; Mohammad Rifat Haider (BMC, 2022)
Abstract Background Hypertension is a major risk factor of cardiovascular diseases, which is the leading cause of premature mortality worldwide. While untreated hypertension heightens the risk of mortality and morbidity among hypertensive individuals, access to hypertension care in low-and-middle income countries has ties with various socioeconomic inequalities. Child brides represent a marginalized group of population who experience various socioeconomic disadvantages. This study investigates whether there exists any disparity in receiving treatment for hypertension between child brides at young adult age and their same-age peers who were married as adults. Methods We obtained data on 22,140 currently married hypertensive women aged 20 to 34 years from the 2015-16 wave of National Family Health Survey (NFHS-4) of India. We estimated multilevel univariate and multivariable logistic regressions to obtain the odds in favor of not receiving treatment for hypertension. We compared the odds for child brides with those of their peers who were married as adults. Results Among the study participants, 72.6% did not receive any treatment for hypertension. While the share was 70.6% among women who were married as adults, it was 4.3 percentage points higher (P < 0.001) among the child brides. Results from the multilevel logistic regressions reveal that adjusted odds of having untreated hypertension for child brides were 1.12 times (95% confidence interval, 1.00-1.25) that of those who were married as adults. Conclusions Our findings show that hypertensive women who were married as children are at greater risk of not receiving hypertension care at young adult age. Therefore, young women who got married in their childhood should be targeted for regular screening and proper referral and treatment to avoid further detrimental effects of elevated blood pressure.